Character-building training curriculum activity based on the perspective of a humanistic curriculum and existentialism philosophy - Taopik Barkah; Babang Robandi (Inovasi Kurikulum, 2024)
Character building is part of developing soft skills, which is an activity that needs to be done to realize superior human resources. In contrast, soft skills are non-academic competencies that become a person's capital to succeed in his career and function in community life. The character-building training curriculum will create a more harmonious, productive, and ethical work environment. The purpose of writing this article is to describe the relationship between the character-building curriculum based on the perspective of the humanistic curriculum model, describe the relationship between the character-building curriculum based on existentialism philosophy, and decrypt the form of activities in the character-building training curriculum. Researchers use descriptive methods to provide an overview of the phenomena and thoughts being studied through documentation and literature studies using relevant data sources from the research topic to conclude. Activities in the character-building training curriculum based on the humanistic curriculum perspective have a role in developing human potential holistically, involving emotional, social, and spiritual aspects, by the parameters that have been in the character-building curriculum consisting of four competencies, namely intrapersonal abilities, interpersonal abilities, organizational abilities, and spiritual abilities. Meanwhile, according to the existentialist perspective, the activities of the character-building curriculum emphasize individual freedom, personal responsibility, and the search for the meaning of life, emphasizing existentialist concepts such as freedom, responsibility, independence, and authenticity. AbstrakPembangunan karakter bagian dari pengembangan soft skills yang menjadi suatu aktivitas yang perlu dilakukan agar terwujudnya sumber daya manusia yang unggul, di mana soft skills merupakan kompetensi non akademik yang menjadi modal seseorang agar dapat mencapai kesuksesan dalam kehidupan kariernya serta berfungsi dalam kehidupan bermasyarakat. Kurikulum pelatihan pembangunan karakter diharapkan dapat menciptakan lingkungan kerja yang lebih harmonis, produktif, dan beretika. Tujuan penulisan artikel ini adalah untuk mendeskripsikan hubungan kurikulum pembangunan karakter berdasarkan perspektif model kurikulum humanistik, mendeskripsikan hubungan kurikulum pembangunan karakter berdasarkan perspektif filsafat eksistensialisme, dan mendeskripsikan bentuk aktivitas dalam kurikulum pelatihan pembangunan karakter. Peneliti menggunakan metode deskriptif yang bertujuan memberikan gambaran tentang fenomena dan pemikiran yang sedang dikaji melalui studi dokumentasi dan kepustakaan menggunakan oleh sumber-sumber data yang relevan sesuai dengan topik penelitian untuk dapat kemudian ditarik kesimpulan. Aktivitas dalam kurikulum pelatihan pembangunan karakter berdasarkan perspektif kurikulum humanistik memiliki peran pada pengembangan potensi manusia secara holistik, melibatkan aspek-aspek emosional, sosial, dan spiritual, sesuai dengan parameter yang selama ini ada dalam kurikulum pembangunan karakter yang terdiri dari empat kompetensi yaitu kemampuan intrapersonal, kemampuan interpersonal, kemampuan organisasional, dan kemampuan spiritual. Sedangkan menurut perspektif eksistensialisme aktivitas dari kurikulum pembangunan karakter menekankan pada kebebasan individu, tanggung jawab pribadi, dan pencarian makna hidup, yang menyangkut konsep eksistensialis, seperti kebebasan, tanggung jawab, mandiri, dan otentik.Kata Kunci: eksistensialisme; kurikulum humanistik; pelatihan; pembangunan karakter